Observation of the size of the lesion during histotripsy according to acoustic parameters - 최지원; 최원석; 김형민; 박혜원; 윤인찬; 한성민 (2025년 제65회 대한의용생체공학회 춘계학술대회, 2025)
Boiling histotripsy (BH) is a non-thermal tissue ablation technique that uses high-intensity focused ultrasound (HIFU) to induce millisecond-long pulses, generating boiling vapor at the focal point. Unlike conventional thermal HIFU, which causes coagulative necrosis and scarring, BH enables precise, mechanical tissue fractionation with minimal collateral damage. The resulting tadpole-shaped lesions vary in size based on BH pulsing parameters. This study evaluates the effect of pulse duration on lesion dimensions using agarose gel phantoms, aiming to improve quantification and optimization of BH treatment outcomes.